Análise espacial multicritério da mesoacessibilidade ao transporte público em João Pessoa/PB - Llanco, Marcelo Chalub (2025)
The growth of urbanization and the pursuit of sustainable solutions for urban mobility, especially in Brazil, highlight the need for efficient public transportation systems. This work analyzes meso-accessibility to public transportation in João Pessoa/PB, focusing on the conditions of the bus system in the vicinity of the Federal University of Paraíba (UFPB), a major travel hub. The research begins with a systematic literature review, following the PRISMA method guidelines, to support the collection of literary data and the formulation of analytical questions. The methodology includes the collection of data from Operational Service Orders (OSO) and multi-criteria spatial analyses, using statistical methods such as sample description of data and Principal Component Analysis (PCA) via the Python programming language, to identify patterns and disparities in access to public transportation. The results reveal that three bus lines face issues of underutilization or overutilization, indicating the need for interventions to ensure equitable and sustainable accessibility. The research identifies critical gaps in accessibility, offering valuable insights for the formulation of public policies that promote social inclusion and improvement of the transportation system. The combination of statistical methods and innovative tools, such as Python, demonstrates the potential of this approach to guide strategic decisions and enhance urban mobility.